Penatalaksanaan Kadar Gula Darah Tikus Putih (Rattus norvegicus) Model Diabetes Mellitus Tipe 2 Menggunakan Rebusan Umbi Yakon (Smallanthus sonchifolius) - Thatit Nurmawati Nurmawati; Anita Rahmawati; Firda Mutiara (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
The world health organization recommends the use of traditional medicines for chronic and degenerative diseases in maintaining health and helping to improve their safety and efficacy. The Yakon (SS) tubers contain FOS (Fructooligosaccharides) as a lowering of blood sugar levels. The purpose of this study was to determine blood sugar levels after treatment with boiled Yakon tubers (SS). This type of research is an experimental design with a pre-post test with a control-group design. The independent variable is the boiled water of Yakon tubers, the dependent variable is blood sugar levels. The samples were divided into 2 groups: the treatment group of boiled Yakon tuber (Smallanthus s) dose 1 (350 mg/kg/BW) and dose 2 (700 mg/kg/BW), the control group. Each group consisted of 6 rats. Mice were conditioned to hyperglycemia by being given a high-glucose diet for 9 weeks. Blood sugar measurement using Gluco-D, data analysis used is Paired Sample T-Test, Independent, Sample T-Test, and One Way Anova. The results showed that treatment dose 1 experienced an average decrease in blood sugar levels by 158.5 mg/dl (p 0.004) and dose 2 by 161.17 mg/dl (p 0.001). The results of the study were the control group and treatment 1 (Sig.2-tailed) = .000 (0.05) and the control group with treatment 2 (Sig.2-tailed) = .000 (0.05) While the comparison results showed that there was a difference between the control group with treatment group 1, and control group with treatment 2 respectively (Sig.2-tailed)=0.000, =0.05. The results of this study indicate that there is an effect of boiled water from Yakon tubers. The Yakon tuber boiled water can be implemented as an alternative in the management of blood sugar in conditions of diabetes mellitus.